Noradrenaline acting at central ?-adrenoceptors induces interleukin-10 and suppressor of cytokine signaling-3 expression in rat brain: Implications for neurodegeneration (2010)
Evidence indicates that the monoamine neurotransmitter noradrenaline elicits anti-inflammatory actions in the central nervous system (CNS), and consequently may play a neuroprotective role where inflammatory events contribute to CNS pathology. Here we examined the ability of pharmacologically enhancing central noradrenergic tone to induce expression of anti-inflammatory cytokines in rat brain. Administration of the noradrenaline reuptake inhibitor reboxetine (15 mg/kg; ip) combined with the ?2-adrenoceptor antagonist idazoxan (1 mg/kg; ip) induced interleukin-10 (IL-10) expression in rat cortex and hippocampus. In addition, these drug treatments induced IL-10 signaling as indicated by increased STAT3 phosphorylation and suppressor of cytokine signaling-3 (SOCS-3) mRNA expression. In contrast to the profound increase in IL-10 induced by the reboxetine/idazoxan combination, the other two broad spectrum anti-inflammatory cytokines IL-4 and TGF-? were not induced by this treatment. The ability of combined treatment with reboxetine and idazoxan to induce IL-10 and SOCS3 expression was mediated by ?-adrenoceptor activation, as their induction was blocked by pre-treatment with the ?-adrenoceptor antagonist propranolol. Moreover, administration of the brain penetrant ?2-adrenoceptor agonist clenbuterol induced a time- and dose-dependent increase in central IL-10 and SOCS3 expression, and the ability of clenbuterol to induce IL-10 and SOCS-3 expression was blocked by the centrally acting ?-adrenoceptor antagonist, propranolol, and was mimicked by the highly selective ?2-adrenoceptor agonist formoterol. In all, these data indicate that increasing central noradrenergic tone induces IL-10 production and signaling in the CNS, which may protect against neurodegeneration.